Modification of Thermal Hydraulic Transient Models for the Miniature Neutron Source Reactor - Abubakar, N.; Garba, I.; Jimoh, M. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
A modified Miniature Neutron Source Reactor (MNSR) model dealing with transient thermal hydraulic problem is presented. The model based on lumped parameter method is adopted in this work to numerically solve a system of coupled algebraic and differential equations governing heat transfer in MNSR, using MATLAB solver for variable order method in stiff differential equations and Differential-Algebraic equations, coupled with Maple soft. The simulated results obtained from the model were generally in agreement when compared with reactor operation data recorded from 0 to 270 minutes during experiments. Radiating energy of Fuel and clad and heat transferred at the gap or clearance were taken in to account. Fuel and clad temperatures as well as various temperatures at different sections of the reactor were predicted with the model, in addition to the effect of the installed chiller on the reactor coolant.